Ancaman atau Peluang? Dinamika dan Volatilitas Nilai Tukar Rupiah Versus Harga Saham di Indonesia - Zakaria, Rinny Apriliany (Lingka Ekonomika, 2025)
From a theoretical standpoint, volatility in the capital market and the foreign exchange market is linked through a bidirectional causal mechanism, underscoring the close interdependence between the rupiah exchange rate and equity prices in Indonesia. This study aims to empirically investigate the nature and dynamics of this relationship, thereby providing robust validation of the interconnection between the two markets. Utilizing a time series framework, specifically the Vector Autoregression (VAR) model, the analysis covers the period from 1995 to 2024. The empirical findings confirm the existence of a two-way causal linkage between the rupiah exchange rate and equity prices, with both markets exhibiting strong and immediate responses to shocks originating in either domain.